Intervening to reduce sedentary behavior in older adults - pilot results - Kelli F. Koltyn; Kevin M. Crombie; Angelique G. Brellenthin; Brianna Leitzelar; Laura D. Ellingson; Jill Renken; Jane E. Mahoney (Tabriz University of Medical Sciences, 2019)
Background: Older adults spend most of their day in sedentary behavior (SB) (i.e., prolonged sitting), increasing risk for negative health outcomes, functional loss, and diminished ability for activities of daily living. The purpose of this study was to develop and pilot test an intervention designed to reduce SB in older adults that could be translated to communities. Methods: Two pilot studies implementing a 4-week SB intervention were conducted. SB,physical function, and health-related quality of life were measured via self-report and objective measures. Participants (N=21) completed assessments pre- and post-intervention (studies 1 and 2) and at follow-up (4-weeks post-intervention; study 2). Due to the pilot nature of this research, data were analyzed with Cohen's d effect sizes to examine the magnitude of change in outcomes following the intervention. Results: Results for study 1 indicated moderate (d=0.53) decreases in accelerometry-obtained total SB and increases (d=0.52) in light intensity physical activity post-intervention. In study 2,there was a moderate decrease (d=0.57) in SB evident at follow-up. On average SB decreased by approximately 60 min/d in both studies. Also, there were moderate-to-large improvements in vitality (d=0.74; study 1) and gait speed (d=1.15; study 2) following the intervention. Further,the intervention was found to be feasible for staff to implement in the community. Conclusion: These pilot results informed the design of an ongoing federally funded randomized controlled trial with a larger sample of older adults from underserved communities. Effective,feasible, and readily-accessible interventions have potential to improve the health and function of older adults.